The Alchemy of Ground - Conger, John (Bioenergetic Analysis, 2016)
The «Alchemy of Ground” is a personal essay about finding home in nature. Paleo-anthropologists tell us that the mineral structure of the earth and water of our childhood home, written into our bones, identifies our homeland. As one client demonstrates, while culturally we are independent and mobile, we hunger for our body’s familiar experience of homeland. More than minerals, the colors of the earth, the guardianship of the trees that think in slow time, the dominance of smell over our artificial sense of time – these draw our bodies back to a communication, deep rhythm and longing for a lost earth, that we split away from and forgot.